Designing creative high power teams and organizations beyond leadership - Stein, Eric W. 1956- (Human resource management and organizational behavior collection, 2014)
The very best firms today are poietic organizations; that is, they are exceptional at streamlining the processes of ideation, creation, and production. Toward that end, poietic organizations do two things well: (1) they design and develop high power teams, and (2) they create an organizational culture and context that supports improvisation, design, experimentation, aesthetic awareness, and strengths development. Great teams exhibit the same characteristics: trust, commitment, and energy. The first half of this book shows the reader how to assess team member strengths using personality factors and multiple intelligences theory. Following the assessments, the book illustrates how to best represent and share this information to promote team development. Three types of high performance teams are examined: improvisational teams, design teams, and research teams. The second half of this book examines the major models and images upon which organizations are constructed, and the pros and cons of these choices. Next, we look at the rise of the poietic organization and its characteristics; that is, ones that innovate on a frequent basis. The differences between ordinary organizations and poietic organizations are highlighted, and why being a poietic organization confers competitive advantage. Finally, we look at ways to transform your organization into a poietic organization. In summary, this book is about how to design and develop creative high power teams and organizations, and explains why some firms lead the way to blue oceans while others languish in red seas.